Pseudopuritanism: Studi Al-Dakhil Atas Tafsir Majelis Tafsir Al-Qur’an (Mta) - Khoirul Umami (FALASIFA : Jurnal Studi Keislaman, 2020)
This study will discuss the ambiguity of the Majelis Tafsir al-Qur'an (MTA) as a missionary organization trying to explore the sacred heirlooms in the form of Islamic law or trying to purify Islamic law, by making MTA interpretations as a reference for their da'wah, in the introduction to their interpretation they will not using the hadith daif, the history of Israel as a reference. However, in reality, they are precisely inconsistent with the principles of the teachings of making the Old Testament as the source of their interpretation. This research is a library research that seeks to explore and explore the interpretations carried out by MTA. Through al-Dhakhil's approach as a study of the theory of criticism of puritan ideological interpretation, it was found that the interpretation of MTA which became the reference of his da'wah, was inconsistent between statements and practice and made the old treaty as a reference in his interpretation and equated with Torah, even though the two were different.